Alcohol Consumption and Tryptophan Metabolism Among People with HIV Prior to Antiretroviral Therapy Initiation: The Uganda ARCH Cohort Study - Pierre, Frantz; Ngabirano, Christine; Emenyonu, Nneka; Muyindike, Winnie; So-Armah, Kaku (Alcohol and Alcoholism, 2022)
Alcohol is hypothesized to have effects on the kynurenine pathway of tryptophan catabolism, a potential mechanism for alcohol-induced depression and aggression. A biomarker of this pathway, the plasma kynurenine to tryptophan ratio (K/T ratio), has been associated with HIV progression, mortality and depression. Our aim was to assess whether hazardous alcohol consumption is associated higher K/T ratio among people with HIV. Participants were a subset of the Uganda Alcohol Research Collaboration on HIV/AIDS Cohort. Alcohol consumption was categorized (abstinent, moderate and hazardous alcohol use) using the Alcohol Use Disorders Identification Test—Consumption and phosphatidylethanol (PEth). K/T ratio was the primary outcome. We used linear regression adjusted for age, sex, FIB-4, hepatitis B surface antigen, log (HIV viral load) to estimate the association between alcohol consumption and K/T ratio. Compared to abstinent participants, hazardous drinkers and moderate drinkers had higher K/T ratio but these differences did not reach statistical significance. Our results suggest that hazardous alcohol consumption, in the context of untreated HIV infection, may not significantly alter kynurenine to tryptophan ratio as a measure of activity of the kynurenine pathway of tryptophan metabolism.